2016
DOI: 10.1002/art.39499
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis IgG Induction of Calcium/Calmodulin‐Dependent Protein Kinase IV Expression in Podocytes and Alteration of Their Function

Abstract: Objective. Kidney podocytes and their slit diaphragms prevent urinary protein loss. T cells from patients with systemic lupus erythematosus display increased expression of calcium/calmodulin-dependent protein kinase IV (CaMKIV). The present study was undertaken to investigate the role of CaMKIV in podocyte function in lupus nephritis (LN). Methods. We treated kidney podocytes with IgG derived from healthy individuals or patients with LN and then analyzed gene expression using a DNA microarray. The localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…One plausible mechanism is that these IgG molecules enter podocytes via neonatal Fc receptor (FcRn). This mechanism is supported by the recent observation that IgG from lupus patients entered podocytes via the FcRn receptor and up-regulated Ca 21 /calmodulindependent protein kinase IV, which was followed by increased expression of genes related to podocyte damage and T cell activation (36). It should be clear that other mechanisms are plausible.…”
Section: Discussionmentioning
confidence: 73%
“…One plausible mechanism is that these IgG molecules enter podocytes via neonatal Fc receptor (FcRn). This mechanism is supported by the recent observation that IgG from lupus patients entered podocytes via the FcRn receptor and up-regulated Ca 21 /calmodulindependent protein kinase IV, which was followed by increased expression of genes related to podocyte damage and T cell activation (36). It should be clear that other mechanisms are plausible.…”
Section: Discussionmentioning
confidence: 73%
“…Pharmacologic inhibition (12) or genetic deletion of CaMK4 (13) and targeted delivery of a CaMK4 inhibitor to CD4 + T cells (14) effectively prevented LN in the lupus-prone MRL.lpr mouse. We have found that CaMK4 was increased and colocalized with nephrin in the glomeruli of SLE patients and that IgG from LN patients upregulated CaMK4 in podocyte cultures (15).…”
Section: Introductionmentioning
confidence: 74%
“…Recently, Haddon et al [43] demonstrated that pediatric SLE patients with kidney involvement possessed a different autoantibody profile than those without kidney involvement. Other groups then showed differences in expression levels of RNA and microRNAs in lupus nephritis biopsies [44, 45], suggesting that different clinical phenotypes may have individualized gene expression signatures.…”
Section: Discussionmentioning
confidence: 99%